Montmorillonite grafted flame retardant modified polystyrene composite material and preparation method thereof

By adding montmorillonite grafting flame retardant to polystyrene, the problem of flammability of polystyrene is solved, and its flame retardant and mechanical properties are significantly improved, forming a composite material with excellent flame retardant properties.

CN119529440AInactive Publication Date: 2025-02-28WUHAN FENGLITIAN TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411788752.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polystyrene materials are flammable and release smoke and toxic gases during combustion, which poses safety risks. How to improve its flame retardant performance is the key.

Method used

By adding a montmorillonite grafting flame retardant to the polystyrene, the specific steps include modifying nanomontmorillonite, grafting hexa(4-aldehyde phenoxy)cyclotriphosphazene and double spirocyclophosphamide to form a montmorillonite grafting flame retardant, and mixing it with polystyrene by melt kneading method.

Benefits of technology

The modified polystyrene composite material delays the migration of oxygen and heat during combustion, reduces the decomposition speed, forms a dense carbon layer, reduces the generation of volatiles, and significantly improves the flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529440A_ABST
    Figure CN119529440A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flame retardance, and discloses a montmorillonite grafted flame retardant modified polystyrene composite material, polystyrene is intercalated into a nano montmorillonite structure in a molten state and is uniformly distributed in a matrix, so that the mechanical property and heat resistance of polystyrene are improved, and when the matrix is burnt, the flame retardancy of polystyrene is improved. Montmorillonite is gradually enriched on the surface of a matrix, a certain blocking effect is generated on interlayer macromolecules, the speed of external oxygen and heat transferring to the interior is reduced, a compact carbon layer is formed, volatile matter is reduced, the good smoke suppression and flame retardant effects are achieved, phosphorus forms the compact carbon layer on the surface of the matrix, and the flame retardant effect is good. The nitrogen element forms incombustible gas, the concentration of oxygen in a reaction system is reduced while polystyrene decomposition is inhibited, the combustion reaction is slowed down, the nitrogen element is uniformly dispersed in a polystyrene matrix, and the obtained composite material has excellent flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardancy, in particular to a montmorillonite grafted flame retardant modified polystyrene composite material and a preparation method thereof. Background Art

[0002] With the continuous development of modern industry, the polymer industry has made great achievements. The scope and proportion of polymer materials in various fields have gradually increased. They are widely used in building materials, transportation, interior decoration and other fields, becoming the basic materials in national economic construction and playing a huge role. However, most polymer materials are flammable and will release a lot of smoke and toxic gases during combustion. At the same time, they burn quickly, which will cause huge safety hazards and threaten people’s property and lives. How to improve the flame retardant properties of polymer materials and obtain green and environmentally friendly flame retardant polymer materials is of great significance.

[0003] As one of the resins with the largest output, polystyrene has a series of advantages such as being non-toxic, harmless, and having good chemical corrosion resistance. It is a polymer material with a wide range of applications. However, the flammable nature of polymer materials limits their use to a certain extent. Adding flame retardants to a polystyrene matrix can effectively improve this shortcoming. CN103333424A discloses "a polystyrene halogen-free environmentally friendly flame retardant and a preparation method thereof". Polyphosphoramide is used as a flame retardant, and expanded graphite and calcium carbonate are added at the same time. The obtained polystyrene has good flame retardant properties. However, these inorganic materials are only added by blending, and the cost of expanded graphite is relatively high. Nano-montmorillonite is low in price and is green and environmentally friendly. As an additive, it can effectively improve the flame retardant properties of the matrix, and at the same time improve the mechanical properties of the matrix. After being grafted with nitrogen and phosphorus halogen-free flame retardants, it is added to a polystyrene matrix, and the obtained composite material has excellent flame retardant properties.

[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a montmorillonite grafted flame retardant modified polystyrene composite material and a preparation method thereof, which solves the problem that polystyrene is flammable.

[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a montmorillonite grafted flame retardant modified polystyrene composite material, the montmorillonite grafted flame retardant modified polystyrene composite material and the preparation method are as follows: (1) Adding ethanol solvent and nano-montmorillonite into a reactor, uniformly dispersing by ultrasonication, then adding 3-aminopropyltriethoxysilane, stirring and mixing, and carrying out a modification reaction at 70-90° C. for 2-5 hours. After the reaction is completed, filtering, washing, and drying to obtain amino-modified nano-montmorillonite; (2) adding ethanol solvent and amino-modified nano-montmorillonite into a reactor, and then adding hexa(4-formylphenoxy)cyclotriphosphazene after ultrasonic dispersion, stirring and mixing to react, and after the reaction is completed, filtering, washing, and drying to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) adding acetonitrile solvent and hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite into a reactor, and after ultrasonic dispersion, adding bis-spirocyclophosphamide, stirring and mixing, heating, reacting, and after the reaction is completed, filtering, washing, and drying to obtain a montmorillonite grafted flame retardant; (4) Add polystyrene resin and montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 160-180° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0006] Preferably, in step (1), the mass ratio of ethanol, nano-montmorillonite and 3-aminopropyltriethoxysilane is 2500-4000:100:220-300.

[0007] Preferably, in step (2), the mass ratio of ethanol, amino-modified nano-montmorillonite and hexa(4-formylphenoxy)cyclotriphosphazene is 1800-2800:100:300-500.

[0008] Preferably, the reaction temperature in step (2) is 20-40° C., and the reaction time is 24-36 h.

[0009] Preferably, in step (3), the mass ratio of acetonitrile, hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite and bisspirocyclophosphamide is 800-1500:100:50-65.

[0010] Preferably, the reaction temperature in step (3) is 40-60° C., and the reaction time is 48-72 h.

[0011] Preferably, in step (4), the mass ratio of the polystyrene resin to the montmorillonite grafted flame retardant is 100:2-6.

[0012] 3. Beneficial technical effects Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a montmorillonite grafted flame retardant modified polystyrene composite material. In a synthesis process, 3-aminopropyltriethoxysilane is used to modify nano-montmorillonite to obtain amino nano-montmorillonite; in an ethanol solvent, the amino group on the amino nano-montmorillonite and the aldehyde group on hexa(4-formylphenoxy)cyclotriphosphazene undergo Schiff base reaction to obtain hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite; in an acetonitrile solvent, the hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite and bis-spirocyclophosphamide undergo hyperbranching reaction; the cyclotriphosphazene is used as a nitrogen source and a phosphorus source to obtain a montmorillonite grafted flame retardant; and in a plasticator, the montmorillonite grafted flame retardant and polystyrene are melt-mixed to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0013] The montmorillonite grafted flame retardant modified polystyrene composite material is prepared by mixing nano-montmorillonite and matrix polystyrene by a melting method, wherein the polystyrene is intercalated into the nano-montmorillonite structure in a molten state, and the formed composite material has good thermoplasticity and is evenly distributed in the matrix, and the mechanical properties and heat resistance of the polystyrene are effectively improved. When the matrix burns, the montmorillonite is gradually enriched on the surface of the matrix, and has a certain barrier effect on the macromolecules between the layers, and effectively slows down the rate at which external oxygen and heat migrate to the inside, and reduces the decomposition rate of the polystyrene. degree, and at the same time form a dense carbon layer, which slows down the transfer of combustion heat to the unburned part, reduces the generation of volatiles, and plays a good role in smoke suppression and flame retardancy. Organic nitrogen-phosphorus flame retardant, during the combustion process, phosphorus element forms a dense carbon layer on the surface of the matrix, and nitrogen element forms non-flammable gas, which inhibits the decomposition of polystyrene while reducing the concentration of oxygen in the reaction system, slowing down the combustion reaction. After grafting with montmorillonite, it can effectively avoid the agglomeration of nano-montmorillonite and can be evenly dispersed in the polystyrene matrix. The obtained composite material has excellent flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the structure of hexa(4-formylphenoxy)cyclotriphosphazene.

[0015] Figure 2 It is a schematic diagram of the structure of bispirocyclophosphamide. DETAILED DESCRIPTION

[0016] To achieve the above object, the present invention provides the following specific implementation methods and examples: A method for preparing a montmorillonite-grafted flame retardant-modified polystyrene composite material is as follows: (1) Adding ethanol solvent and nano-montmorillonite into a reactor, and then adding 3-aminopropyltriethoxysilane after ultrasonic dispersion, wherein the mass ratio of the added ethanol, nano-montmorillonite and 3-aminopropyltriethoxysilane is 2500-4000:100:220-300, stirring and mixing, and performing a modification reaction at 70-90° C. for 2-5 hours. After the reaction is completed, filtering, washing with deionized water and ethanol, and drying to obtain amino-modified nano-montmorillonite; (2) adding ethanol solvent and amino-modified nano-montmorillonite into a reactor, and then adding hexa(4-formylphenoxy)cyclotriphosphazene after ultrasonic dispersion, wherein the mass ratio of the added ethanol, amino-modified nano-montmorillonite and hexa(4-formylphenoxy)cyclotriphosphazene is 1800-2800:100:300-500, stirring and mixing, reacting at 20-40° C. for 24-36 hours, filtering, washing with ethanol, and drying to obtain hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite; (3) Add acetonitrile solvent and hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite into the reactor, and after ultrasonic dispersion, add bis-spiro cyclophosphamide, wherein the mass ratio of acetonitrile, hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite and bis-spiro cyclophosphamide is 800-1500:100:50-65, stir and mix evenly, heat, react at 40-60°C, and react for 48-72h. After the reaction is completed, filter, wash with ethyl acetate, and dry to obtain a montmorillonite grafted flame retardant; (4) Add polystyrene resin and montmorillonite grafted flame retardant in a mass ratio of 100:2-6 into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 160-180° C. After mixing, cool and discharge to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0017] Example 1

[0018] (1) Add 250 g of ethanol solvent and 10 g of nano-montmorillonite into a reactor, disperse them uniformly by ultrasonication, then add 22 g of 3-aminopropyltriethoxysilane, stir and mix, and perform a modification reaction at 70 °C for 2 h. After the reaction is completed, filter, wash with deionized water and ethanol, and dry to obtain amino-modified nano-montmorillonite; (2) Add 180 g of ethanol solvent and 10 g of amino-modified nano-montmorillonite into the reactor, and after ultrasonic dispersion, add 30 g of hexa(4-formylphenoxy)cyclotriphosphazene, stir and mix, and react at 20° C. for 24 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) Add 80g of acetonitrile solvent and 10g of hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite into the reactor, disperse them uniformly by ultrasonication, then add 5g of bis-spirocyclophosphamide, stir and mix uniformly, heat, react at 40°C, and react for 48h. After the reaction is completed, filter, wash with ethyl acetate, and dry to obtain a montmorillonite grafted flame retardant; (4) Add 100 g of polystyrene resin and 2 g of montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 160° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0019] Example 2

[0020] (1) Add 280 g of ethanol solvent and 10 g of nano-montmorillonite into a reactor, disperse them uniformly by ultrasonication, then add 24 g of 3-aminopropyltriethoxysilane, stir and mix, and perform a modification reaction at 75 °C for 3 h. After the reaction is completed, filter, wash with deionized water and ethanol, and dry to obtain amino-modified nano-montmorillonite; (2) Add 200 g of ethanol solvent and 10 g of amino-modified nano-montmorillonite into the reactor, disperse them uniformly by ultrasonication, then add 35 g of hexa(4-formylphenoxy)cyclotriphosphazene, stir and mix, react at 25° C. for 28 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) Add 100 g of acetonitrile solvent and 10 g of hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite into the reactor, disperse them uniformly by ultrasonication, then add 5.5 g of bis-spirocyclophosphamide, stir and mix them uniformly, heat and react at 45°C for 54 h. After the reaction is completed, filter and wash with ethyl acetate, and dry to obtain a montmorillonite-grafted flame retardant. (4) Add 100 g of polystyrene resin and 3 g of montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 165° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0021] Example 3

[0022] (1) Add 300 g of ethanol solvent and 10 g of nano-montmorillonite into a reactor, disperse them uniformly by ultrasonication, then add 25 g of 3-aminopropyltriethoxysilane, stir and mix, and perform a modification reaction at 80° C. for 3 h. After the reaction is completed, filter, wash with deionized water and ethanol, and dry to obtain amino-modified nano-montmorillonite; (2) Add 220 g of ethanol solvent and 10 g of amino-modified nano-montmorillonite into the reactor, disperse them uniformly by ultrasonication, then add 40 g of hexa(4-formylphenoxy)cyclotriphosphazene, stir and mix, react at 30° C. for 30 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) Add 120 g of acetonitrile solvent and 10 g of hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite into the reactor, disperse them uniformly by ultrasonication, add 6 g of bis-spirocyclophosphamide, stir and mix uniformly, heat, react at 50°C, and react for 60 h. After the reaction is completed, filter, wash with ethyl acetate, and dry to obtain a montmorillonite-grafted flame retardant; (4) Add 100 g of polystyrene resin and 4 g of montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 170° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0023] Example 4

[0024] (1) Add 350 g of ethanol solvent and 10 g of nano-montmorillonite into a reactor, disperse them uniformly by ultrasonication, then add 28 g of 3-aminopropyltriethoxysilane, stir and mix, and perform a modification reaction at 85 °C for 4 h. After the reaction is completed, filter, wash with deionized water and ethanol, and dry to obtain amino-modified nano-montmorillonite; (2) Add 250 g of ethanol solvent and 10 g of amino-modified nano-montmorillonite into the reactor, and after uniform ultrasonic dispersion, add 45 g of hexa(4-formylphenoxy)cyclotriphosphazene, stir and mix, and react at 35° C. for 32 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) Add 140 g of acetonitrile solvent and 10 g of hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite into the reactor, disperse them uniformly by ultrasonication, then add 6.2 g of bis-spirocyclophosphamide, stir and mix uniformly, heat, react at 55°C, and react for 65 h. After the reaction is completed, filter, wash with ethyl acetate, and dry to obtain a montmorillonite-grafted flame retardant; (4) Add 100 g of polystyrene resin and 5 g of montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 175° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0025] Example 5

[0026] (1) Add 400 g of ethanol solvent and 10 g of nano-montmorillonite into a reactor, disperse them uniformly by ultrasonication, then add 30 g of 3-aminopropyltriethoxysilane, stir and mix, and perform a modification reaction at 90° C. for 5 h. After the reaction is completed, filter, wash with deionized water and ethanol, and dry to obtain amino-modified nano-montmorillonite; (2) Add 280 g of ethanol solvent and 10 g of amino-modified nano-montmorillonite into the reactor, and after ultrasonic dispersion, add 50 g of hexa(4-formylphenoxy)cyclotriphosphazene, stir and mix, and react at 40° C. for 36 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) Add 150 g of acetonitrile solvent and 10 g of hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite into the reactor, disperse them uniformly by ultrasonication, then add 6.5 g of bis-spirocyclophosphamide, stir and mix uniformly, heat, react at 60°C, and react for 72 h. After the reaction is completed, filter, wash with ethyl acetate, and dry to obtain a montmorillonite-grafted flame retardant; (4) Add 100 g of polystyrene resin and 6 g of montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 180° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

[0027] Comparative Example 1 (1) Add 350 g of ethanol solvent and 10 g of nano-montmorillonite into a reactor, disperse them uniformly by ultrasonication, then add 25 g of 3-aminopropyltriethoxysilane, stir and mix, and perform a modification reaction at 80° C. for 4 h. After the reaction is completed, filter, wash with deionized water and ethanol, and dry to obtain amino-modified nano-montmorillonite; (2) Add 100 g of polystyrene resin and 4 g of amino-modified nano-montmorillonite into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 170° C. After mixing, cool and discharge the mixture to obtain a montmorillonite-modified polystyrene composite material.

[0028] The polystyrene composite materials synthesized in the examples and comparative examples were added to a flat vulcanizer and molded into 3 mm plates at 185° C. The plates were cut into strips of 100 mm×100 mm×3 mm and placed on a JF-5 fully automatic oxygen index instrument for limiting oxygen index testing.

[0029] The polystyrene composite materials synthesized in the examples and comparative examples were added to a flat vulcanizer and molded into 3 mm plates at 185° C. The plates were cut into strips of 100 mm×100 mm×3 mm and placed on a ZY6243 cone calorimeter for heat release rate testing.

Claims

1. A montmorillonite-grafted flame retardant-modified polystyrene composite material, characterized in that: The montmorillonite grafted flame retardant modified polystyrene composite material and preparation method are as follows: (1) Adding ethanol solvent and nano-montmorillonite into a reactor, uniformly dispersing by ultrasonication, then adding 3-aminopropyltriethoxysilane, stirring and mixing, and carrying out a modification reaction at 70-90° C. for 2-5 hours. After the reaction is completed, filtering, washing, and drying to obtain amino-modified nano-montmorillonite; (2) adding ethanol solvent and amino-modified nano-montmorillonite into a reactor, and then adding hexa(4-formylphenoxy)cyclotriphosphazene after ultrasonic dispersion, stirring and mixing to react, and after the reaction is completed, filtering, washing, and drying to obtain hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite; (3) adding acetonitrile solvent and hexa(4-formylphenoxy)cyclotriphosphazene grafted montmorillonite into a reactor, and after ultrasonic dispersion, adding bis-spirocyclophosphamide, stirring and mixing, heating, reacting, and after the reaction is completed, filtering, washing, and drying to obtain a montmorillonite grafted flame retardant; (4) Add polystyrene resin and montmorillonite grafted flame retardant into a high-speed mixer, mix well, transfer to a plasticator, and perform melt mixing at 160-180° C. After mixing, cool and discharge the material to obtain a montmorillonite grafted flame retardant modified polystyrene composite material.

2. The montmorillonite-grafted flame retardant-modified polystyrene composite material according to claim 1, characterized in that: In the step (1), the mass ratio of ethanol, nano-montmorillonite and 3-aminopropyltriethoxysilane is 2500-4000:100:220-300.

3. The montmorillonite-grafted flame retardant-modified polystyrene composite material according to claim 1, characterized in that: In the step (2), the mass ratio of ethanol, amino-modified nano-montmorillonite and hexa(4-formylphenoxy)cyclotriphosphazene is 1800-2800:100:300-500.

4. The montmorillonite-grafted flame retardant-modified polystyrene composite material according to claim 1, characterized in that: The reaction temperature in step (2) is 20-40° C. and the reaction time is 24-36 hours.

5. The montmorillonite-grafted flame retardant-modified polystyrene composite material according to claim 1, characterized in that: In the step (3), the mass ratio of acetonitrile, hexa(4-formylphenoxy)cyclotriphosphazene-grafted montmorillonite and bis-spirocyclophosphamide is 800-1500:100:50-65.

6. The montmorillonite-grafted flame retardant-modified polystyrene composite material according to claim 1, characterized in that: The reaction temperature in step (3) is 40-60° C. and the reaction time is 48-72 hours.

7. The montmorillonite-grafted flame retardant-modified polystyrene composite material according to claim 1, characterized in that: In the step (4), the mass ratio of the polystyrene resin to the montmorillonite grafted flame retardant is 100:2-6.

Citation Information

Patent Citations

  • Halogen-free environment-friendly polystyrene flame retardant and preparation method thereof

    CN103333424A